Environmental dynamics of hospital microbiome upon transfer from a major hospital to a new facility. Issue 6 (December 2021) - Ashokan, Anushia; Choo, Jocelyn M.; Taylor, Steven L.; Lagana, Diana; Shaw, David R.; Warner, Morgyn S.; Wesselingh, Steve L.; Rogers, Geraint B.
Highlights: A strong link was found between occupancy and the level of environmental bacteria. A rise in human microbiota-associated taxa was observed with occupancy. Microbiota characteristics were similar between hospitals at equal occupancy. Similar detection rate of Methicillin-resistant S taphylococcus aureus at both sites. Summary: Background: Infection control is critical to safe hospital care. However, how bacteria within nosocomial environments relate to space utilisation and occupancy remains poorly understood. Our aim was to characterise the hospital microbiome in the context of the closure of a tertiary hospital and the opening of a new facility. Methods: Environmental swabs were collected from common and inpatient areas in the old and new hospitals during a 12-month transition period. Microbiota characteristics were determined by 16S rRNA gene sequencing and quantitative (q)PCR. Targeted assays were used to detect Methicillin-resistant Staphylococcus aureus (MRSA) and vanB -positive Vancomycin-Resistant Enterococci (VRE). Results: The transition to full occupancy in the new facility was associated with an increase in bacterial load (inpatient areas, 3 months p  = 0.001; common areas, 6 months p  = 0.039) and a change in microbiota composition (baseline-12 months, PERMANOVA p  = 0.002). These changes were characterised by an increase in human microbiota-associated taxa, including Acinetobacter and Veillonella . Closure of the existing facility was associated with a decrease in bacterial load ( p  = 0.040). Detection of MRSA did not differ significantly between sites. Conclusions: Occupancy is a major determinant of bacterial dispersion within hospital environments. Steady-state bacterial levels and microbiota composition provide a basis for assessment of infection control measures.